2012
DOI: 10.1515/hf-2012-0017
|View full text |Cite
|
Sign up to set email alerts
|

Topochemistry of heat-treated and N-methylol melamine-modified wood of koto (Pterygota macrocarpa K. Schum.) and limba (Terminalia superba Engl. et. Diels)

Abstract: To broaden the knowledge about the chemical changes at the cell wall level of differently modified tropical hardwoods, heat-treated and N-methylol melamine (NMM)-treated samples of koto (Pterygota macrocarpa) and limba (Terminalia superba) were prepared. UV microspectrophotometry (UMSP) was applied at 278 and 240 nm as specific wavelengths to analyze chemical alterations of the samples caused by heat and NMM treatment, respectively. The absorbance of koto exceeded that of limba before and after treatment, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…The highest absorbances occur in the area of the CML and the CC as previously described for W untr (Koch and Kleist 2001;Koch and Grünwald 2004) and also for thermally (Mahnert et al 2013) and hydrothermally modified wood (Andersons et al 2016). For the W untr tissue, the following UV absorption data (A 280 nm ) are typical: 1.22 for the CML, 1.48 for the CC and lower, slightly varying values for the S2 layer (0.69-0.95).…”
Section: Uv Microscopic Scanning Profilessupporting
confidence: 67%
See 2 more Smart Citations
“…The highest absorbances occur in the area of the CML and the CC as previously described for W untr (Koch and Kleist 2001;Koch and Grünwald 2004) and also for thermally (Mahnert et al 2013) and hydrothermally modified wood (Andersons et al 2016). For the W untr tissue, the following UV absorption data (A 280 nm ) are typical: 1.22 for the CML, 1.48 for the CC and lower, slightly varying values for the S2 layer (0.69-0.95).…”
Section: Uv Microscopic Scanning Profilessupporting
confidence: 67%
“…Compared to W untr , higher UV absorbances were also observed by UMSP on thermally modified wood (160°C-180°C) (Mahnert et al 2013). Andersons et al (2016) reported similar results at lower temperatures, but at 140°C for 1 h only a slight impact on the UV absorbance was seen.…”
Section: Uv Microscopic Scanning Profilesmentioning
confidence: 75%
See 1 more Smart Citation
“…The appearance of silver fir TMW 4 h, 220°C after staining with KMnO 4 is shown in Figure 2 Brought to you by | Sveriges Lantbruksuniversitet Authenticated Download Date | 8/6/15 3:11 PM studies in terms of the apparent lignin content increment in TMWs (Boonstra and Tjeerdsma 2006;Windeisen and Wegener 2008;Esteves and Pereira 2009;Mahnert et al 2013). Esteves and Pereira (2009) emphasized that the apparent high lignin content is the result of polycondensation reactions between lignin and other cell wall components.…”
Section: Lignin Cytochemistry and Ultrastructure Of CML Cc Regionsmentioning
confidence: 99%
“…The changes in the gross chemistry after TM were also extensively studied as reviewed by Esteves and Pereira (2009). Microredistribution of wood components caused by TM was observed by Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR), X-ray photoelectron spectroscopy (XPS), and ultraviolet microspectrophotometry (UMSP) (Sivonen et al 2002;Tjeerdsma and Militz 2005;Kocaefe et al 2012;Mahnert et al 2013). However, these methods also have limitations concerning changes at the cellular level, particularly on individual cell wall layers.…”
Section: Introductionmentioning
confidence: 99%